Linalool Ameliorates Memory Loss and Behavioral Impairment Induced by REM-Sleep Deprivation through the Serotonergic Pathway - Lee, Bo Kyung; Jung, An Na; Jung, Yi-Sook (Biomolecules & therapeutics, 2018)
Rapid eye movement (REM) sleep has an essential role in the process of learning and memory in the hippocampus. It has been reported that linalool, a major component of , has antioxidant, anti-inflammatory, and neuroprotective effects, along with other effects. However, the effect of linalool on the cognitive impairment and behavioral alterations that are induced by REM-sleep deprivation has not yet been elucidated. Several studies have reported that REM-sleep deprivation-induced memory deficits provide a well-known model of behavioral alterations. In the present study, we examined whether linalool elicited an anti-stress effect, reversing the behavioral alterations observed following REM-sleep deprivation in mice. Furthermore, we investigated the underlying mechanism of the effect of linalool. Spatial memory and learning memory were assessed through Y maze and passive avoidance tests, respectively, and the forced swimming test was used to evaluate anti-stress activity. The mechanisms through which linalool improves memory loss and behavioral alterations in sleep-deprived mice appeared to be through an increase in the serotonin levels. Linalool significantly ameliorated the spatial and learning memory deficits, and stress activity observed in sleep-deprived animals. Moreover, linalool led to serotonin release, and cortisol level reduction. Our findings suggest that linalool has beneficial effects on the memory loss and behavioral alterations induced by REM-sleep deprivation through the regulation of serotonin levels.